2015
DOI: 10.1007/7355_2015_93
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the C-Terminus of Hsp90 as a Cancer Therapy

Abstract: Classical Hsp90 inhibitors target the N-terminal ATP binding site. While these inhibitors have had some clinical success, treatment with these molecules leads to a dramatic increase in a set of stress-related proteins, a response that is referred to as a heat shock response. The induction of a heat shock response protects the cell against the protein aggregation induced by inhibiting Hsp90 and slows down cell death. Alternatively, inhibiting Hsp90 by modulating the C-terminus does not lead to a heat shock resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 89 publications
1
2
0
Order By: Relevance
“…Based on these reports and our findings, we think that Chaetocin inhibits Hsp90 displays stronger inhibitory activity on Hsp90 than on SUV39H1, indicating that Chaetocin inhibits Hsp90. Our results also supported that Chaetocin bound to the C-terminal of Hsp90, as inhibition of Hsp90 by targeting its N-terminus but not its C-terminus is often compensated by increased expression of Hsp70 ( Mcconnell et al ., 2015 ). Previous studies showed that C-terminal inhibitors inhibit the anti-aggregation function of C-terminus of Hsp90α ( Allan et al ., 2006 ).…”
Section: Discussionsupporting
confidence: 83%
“…Based on these reports and our findings, we think that Chaetocin inhibits Hsp90 displays stronger inhibitory activity on Hsp90 than on SUV39H1, indicating that Chaetocin inhibits Hsp90. Our results also supported that Chaetocin bound to the C-terminal of Hsp90, as inhibition of Hsp90 by targeting its N-terminus but not its C-terminus is often compensated by increased expression of Hsp70 ( Mcconnell et al ., 2015 ). Previous studies showed that C-terminal inhibitors inhibit the anti-aggregation function of C-terminus of Hsp90α ( Allan et al ., 2006 ).…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, targeting the chaperoning function of a key host protein, such as Hsp90, could have some potential drawbacks. These include toxicity issues associated with the induction of heat shock response, which is one of the main reasons why Hsp90 inhibitors that have undergone clinical trials have not yet been approved for therapeutic use [30,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is general agreement that an effective drug must modulate Hsp90 through an alternative mechanism, one that does not induce a cytoprotective response. Targeting the CTD of Hsp90 is one such promising strategy. , …”
mentioning
confidence: 99%